2015
DOI: 10.1080/03630242.2015.1118722
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of misperception of breast cancer risk among Korean-American Women

Abstract: This study investigated the factors associated with misperception of breast cancer risk, including unrealistic optimism and unrealistic pessimism, among Korean-American women (KAW). Baseline data were collected between March 2010 and October 2011 from 421 KAW aged 40–65 years who participated in a community-based randomized intervention trial designed to promote breast and cervical cancer screening. Multivariate multinomial regression was performed to identify correlates of misperception of breast cancer risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, this difference favored the high cancer-worry control group with regard to breast self-examination in month 3. Kim et al 33 found that women with high levels of cancer worries had unrealistic pessimism. Negative beliefs surrounding cancer treatment or survival may mean that they do not want to know about the cancer in advance, and this can negatively affect their behavior in relation to obtaining early diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference favored the high cancer-worry control group with regard to breast self-examination in month 3. Kim et al 33 found that women with high levels of cancer worries had unrealistic pessimism. Negative beliefs surrounding cancer treatment or survival may mean that they do not want to know about the cancer in advance, and this can negatively affect their behavior in relation to obtaining early diagnosis of cancer.…”
Section: Discussionmentioning
confidence: 99%